About waste-free processing of saline aluminum slags - Конько, Олег Иванович; Курис, Юрий Владимирович; Грицай, Владимир Петрович (Eastern-European Journal of Enterprise Technologies, 2012)
Explored ways to complete processing of aluminum salt slag. Considered processing technology to produce commercial products in different industries